Lipid remodeling in acrosome exocytosis: unraveling key players in the human sperm - Suhaiman, Laila; Belmonte, Silvia A. (Frontiers in Cell and Developmental Biology, 2024)
It has long been thought that the exocytosis was driven exclusively by well-studied fusion proteins. Some decades ago, the role of lipids became evident and escalated interest in the field. Our laboratory chose a particular cell to face this issue: the human sperm. What makes this cell special? Sperm, as terminal cells, are characterized by their scarcity of organelles and the complete absence of transcriptional and translational activity. They are specialized for a singular membrane fusion occurrence: the exocytosis of the acrosome. This unique trait makes them invaluable for the study of exocytosis in isolation. We will discuss the lipids' role in human sperm acrosome exocytosis from various perspectives, with a primary emphasis on our contributions to the field. Sperm cells have a unique lipid composition, very rare and not observed in many cell types, comprising a high content of plasmalogens, long-chain, and very-long-chain polyunsaturated fatty acids that are particular constituents of some sphingolipids. This review endeavors to unravel the impact of membrane lipid composition on the proper functioning of the exocytic pathway in human sperm and how this lipid dynamic influences its fertilizing capability. Evidence from our and other laboratories allowed unveiling the role and importance of multiple lipids that drive exocytosis. This review highlights the role of cholesterol, diacylglycerol, particular phospholipids like phosphatidic acid, phosphatidylinositol 4,5-bisphosphate, and sphingolipids in driving sperm acrosome exocytosis. Further, we provide a comprehensive overview of the factors and enzymes that regulate lipid turnover during the exocytic course. A more thorough grasp of the role played by lipids transferred from sperm